Effective Intervention to Enhance Understanding in Mathematics: Report of a Successful Experiment - Ganeshan, Lalitha (INDIAN EDUCATIONAL REVIEW, 2013)
Teaching the first year undergraduate students, the foundations of mathematics, is a challenge and could be quite unnerving to a novice. The first few lectures in the First Year B. Sc. class are very crucial and the way in which one handles this will set the tone for the whole year. There are several reasons for this: the fall in enrollment for pure sciences including Mathematics resulting in the poor quality of students opting for Mathematics, their differing needs, and the disparate levels of language skills and mathematical capabilities. But a good number of these students end up teaching Science/Mathematics in high school/higher secondary school and some of them do post graduation and teach in undergraduate colleges and engineering colleges too. So it is imperative that we target this group and try and motivate them, and teach them. Mathematics in a more effective manner. This is a report of a successful intervention since June 2006, using certain strategies to tackle these issues and enhance Mathematics learning, and the understanding of average learners of Mathematics.